(untitled) (Research, Society and Development, 2021)
Introduction: Suicide is a complex phenomenon that can be defined as self-inflicted violence. It’s a public health problem. The dentist, having a bond with his patients, may be the first to witness the signs of suicidal behavior. Objective: to describe the conduct of the dental surgeon in face of suicidal behavior. Methods: This is an exploratory descriptive study with a quantitative approach. Data collection took place through a Whatsapp group, entitled “Dentistas de Divinópolis”. The contact was made through a message sent in the private of each member. The message had an explanation of the project and a link to access the research. Results: 77 professionals participated in this research. Of the 77, 51.9% were male, 68.8% were married or in a stable relationship and 80.5% declared themselves white. 66.2% had specialization, 83.1% worked in the private sector, 39.0% had up to 5 years of training and 96.1% had never received training on the subject. 54.5% were trained under the perspective of the new DCN. A difference was found between single/divorced and married in the Right to Suicide factor. Singles/divorced people have the most moral judgment on this issue. Conclusions: This work becomes relevant since the QUACS is used for the first time with dentists. This is a nationally unprecedented survey related to suicide and the dentist. It is believed that this study will bring a new look to this professional training, as well as a change in the look of the context of suicidal behavior.